2008
DOI: 10.1007/s10815-008-9205-6
|View full text |Cite
|
Sign up to set email alerts
|

The decrease of serum luteinizing hormone level by a gonadotropin-releasing hormone antagonist following the mild IVF stimulation protocol for IVF and its clinical outcome

Abstract: Purpose While performing the mild ovarian stimulation protocol with a GnRH antagonist, the pregnancy rate was compared between the groups, which were divided by the degree that the luteinizing hormone (LH) level decreased. Materials and methods Patients aged 27 to 42years (36.1 ± 3.79) underwent 308 IVF cycles who opted for IVF via the mild ovarian stimulation protocol began clomiphene citrate on day 3 and recombinant FSH on day 5. A GnRH antagonist was administered when the dominant follicle reached 14mm. Ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
(38 reference statements)
2
16
0
1
Order By: Relevance
“…The clinical pregnancy rate of 14.1% per started cycle and 23.5% per ET were achieved. These results are similar to those reported in the previous studies [22,[32][33][34] . The live birth rates in this study were 10.6% per cycle and 17.7% per ET.…”
Section: Discussionsupporting
confidence: 93%
“…The clinical pregnancy rate of 14.1% per started cycle and 23.5% per ET were achieved. These results are similar to those reported in the previous studies [22,[32][33][34] . The live birth rates in this study were 10.6% per cycle and 17.7% per ET.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, a high endogenous LH concentration on days 7/8 of a long protocol stimulation was found to lead to significantly higher oocyte yield and number of available embryos, whereas a sharp drop of serum LH level during the mid-follicular phase was associated with a significantly lower live birth rate in IVF [19]. Similarly, a study on IVF patients undergoing mild ovarian stimulation protocol with GnRH-antagonist reported that the pregnancy and implantation rates were significantly lower if the serum LH levels were low in the late follicular phase [25]. We designed the present study to prospectively analyse IVF outcome in a large series of patients randomized to receive exogenous LH from day 1 or from day 7 of an ovarian stimulation cycle for IVF.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it was previously shown that when in CC/Gn/GnRH-ant cycles the circulating LH is less than one-third at the time of hCG than at the beginning of stimulation, both the pregnancy and implantation rates are significantly reduced [23].…”
Section: Discussionmentioning
confidence: 99%